SURVEI TENTANG SIKAP SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (SISWA KELAS V SDN KEDUNGMUNGAL, KEC. PUNGGING, KAB. MOJOKERTO) - CIPTO HADIYAH, HENRIK (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Sport, physical, and health education, (Penjasorkes), is a lesson in school that is not only aimed to take care of the students’ health and freshness but also aimed as a media to instill the sport values consisting in it.That values are politeness, sincerity, discipline, sportivity, responsibility, never give up, and healthy lifestyle.The target of this research is to know how students’ attitude in the study of penjasorkes. This research belongs to Quantitative Descriptive research. The sample of this research is all the fifth grade students of SDN Kedungmungal, Pungging, Mojokerto. The result of the survey indicated that the students’ attitude in the study of penjasorkes is very good. It can be known from the attitude indicator including discipline, self-confidence, sincerity, cooperation, never give up, leadership, tolerance, self-control, respecting the teacher and responsibility. They are all in good category. The average percentage of the overall student attitude in the study of penjasorkes is 68.72%. The highest percentage for the students’ attitude is in never give up indicator which reach up to 79,3%. Keywords : Teaching and learning process of Penjasorkes, Attitude, Students of SD.